Study of Protein Structures under the Influence of Imidazolium Based Ionic Liquids: A Mini Review - Mandal, Pritha; R. Molla, Anisur (Asian Journal of Chemistry, 2022)
Ionic liquids are nowadays extremely popular in the advanced research field of many disciplines including chemistry, chemical engineering, material science, biology and pharmaceuticals. Unique physico-chemical properties of the ionic liquids such as low vapor pressure, stability, large liquid range, broad solubility and easy modification of structures are responsible for its vast application. Imidazolium based ionic liquids are one of the most widely used ionic liquids and theses are extensively studied in the field of protein research. In this mini-review, imidazolium ionic liquid induced effect on the structure and function of protein molecules are discussed.